(untitled) - Whyte, Anne V. T. (Geneva, 2000)
The draft was then reviewed by more than 40 experts whose comments and recommendations have considerably improved this guide book.
Keywords: Municipal water supply,Sewage disposal,Water-supply,Sanitation,Hệ thống vệ sinh,Cung cấp mước; Citizen participation,Citizen participation,Citizen participation,Citizen participation; Developing countries,Developing countries,Developing countries,Developing countries,Nước đang phát triển,Nước đang phát triển